A nomogram to predict non–sentinel lymph node metastasis in patients with initial cN+ breast cancer that downstages to cN0 after neoadjuvant chemotherapy. Issue 3 (20th May 2020) - Cheng, Minyi; Zhuang, Xiaosheng; Zhang, Liulu; Zhu, Teng; Lin, Yufeng; Yang, Mei; Ji, Fei; Yang, Ciqiu; Gao, Hongfei; Wang, Kun
Abstract: Background and Objectives: This study mainly explored the factors that influence non–sentinel lymph node (NSLN) metastasis in patients with breast cancer (BC) whose axillary lymph nodal status changed from clinically node positive (cN+) to clinically node negative (cN0) after neoadjuvant chemotherapy (NAC). Methods: We retrospectively analyzed the clinicopathological factors affecting NSLN metastasis in a total of 179 patients with cN+ BC downstaged to cN0 (120 in the training set and 59 in the validation set) who underwent both sentinel lymph node (SLN) biopsy and axillary lymph node dissection following NAC. Results: Among 179 patients enrolled, the overall NSLN metastatic rate was 24.0% (95% confidence interval [CI]: 17.7%‐30.3%). In multivariate logistic regression analysis, the number of positive SLNs achieving a pathological complete remission of the breast and clinical node staging was independent predictors of NSLN metastasis. A nomogram was established based on these factors and displayed a good discriminatory capability, with an area under the curve of 0.919 (95% CI: 0.865‐0.973) for the training set and 0.900 (95% CI: 0.812‐0.988) for the validation set and its clinical utility was confirmed by the decision curve analysis. Conclusions: The nomogram established showed the ability to predict NSLN metastases in patients with initial cN+ BC that downstaged to cN0 after NAC.